2013
DOI: 10.1038/aja.2012.143
|View full text |Cite
|
Sign up to set email alerts
|

Trends in global semen parameter values

Abstract: llegations for a worldwide decline in semen parameter values have not withstood scientific scrutiny. Methodological flaws in an influential 1992 paper are summarized here, and studies that have been published since 1992 are reviewed. Of the 35 major studies of time trends in semen quality reviewed here, eight (a total of 18 109 men) suggest a decline in semen quality; 21 (112 386 men) show either no change or an increase in semen quality; and six (26 007 men) show ambiguous or conflicting results. The cause (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 48 publications
0
14
0
3
Order By: Relevance
“…Although some recent studies have corroborated this decline in semen quality [31][32][33], others have found no such change [34,35]. The ambiguity on the issue of sperm count decline has been discussed in an interesting review article by Pacey [36].…”
Section: Fertility Decline-loss Of Sperm Function?mentioning
confidence: 90%
“…Although some recent studies have corroborated this decline in semen quality [31][32][33], others have found no such change [34,35]. The ambiguity on the issue of sperm count decline has been discussed in an interesting review article by Pacey [36].…”
Section: Fertility Decline-loss Of Sperm Function?mentioning
confidence: 90%
“…An evolving body of evidence suggests that decreased semen quality could be related to environmental exposure to oestrogen-like compounds, although some studies have demonstrated conflicting results [144]. Data from randomized human studies show a clear and consistent decline in serum T levels in healthy American men over the years [145], but the trend in the decline in serum T concentration in EDC-exposed men has been more uniform [144].…”
Section: Novel Aspects Of Oestrogen Action In Malesmentioning
confidence: 99%
“…Data from randomized human studies show a clear and consistent decline in serum T levels in healthy American men over the years [145], but the trend in the decline in serum T concentration in EDC-exposed men has been more uniform [144]. Reports have shown lower general sperm counts in Japanese men compared with Caucasian men, which could be associated with the massive consumption of phytoestrogens in Asia, although correlations with other factors, such as genetic diversity or lifestyle issues, cannot be ruled out [146,147].…”
Section: Novel Aspects Of Oestrogen Action In Malesmentioning
confidence: 99%
“…He also concurs with other authors that such comparisons are unsound because of systematic errors reflecting the fact that methods of laboratory Andrology have changed considerably since the 1950s, with developments in training and competence, emphasis on Quality Assurance and Quality Control, and attempts at standardisation of technique. With Nieschlag and Lerchl, 8 Pastuszak and Lamb 7 and Fisch and Braun, 5 he agrees that the only large prospective study carried out to date, overlooking the problem of uncontrolled sampling, shows no change in sperm concentration over 15 years. He argues that this supports the contention that when laboratory methods are adequately controlled, no secular change in sperm counts are observed.…”
mentioning
confidence: 96%